Anthropologists : a tribute to hundred selected contributors to the anthropological discipline - Sukla Sikder (Maya, 2019)
Anthropology as a discipline is something more than whatever has been considering by most of the learner of Anthropology or of other disciplines. As per the visionary depth of this vast discipline, everything on the earth or surrounding the earth related to human are the matter of concern for Anthropology and Anthropology studies all the things through the lenses of time and space regardless of society and culture. While the visionaries say Anthropology began from the time of generation of the environment and then on the commencement of life on the earth which, consequently contributed to the appearance and development of man on the earth through the gradual process of evolution both biological and cultural. Anthropology can trace its association everywhere with human activities and human thoughts and has something to contribute in these spheres. Though formal recognition and institutional association to the discipline came late Anthropology was everywhere on the earth even before it has been named. Nevertheless, the formal framework of Anthropology derives Anthropology as the science or the study of man and it studies the emergence and development of man from physical, cultural and social points of view. Present formal discourse enunciates that Anthropologists are Anthropological thinkers. Anthropologists seek the answer to an enormous variety of questions about humans. They are interested in unveiling when, where and why humans appeared on the earth, how and why they have changed since then, and how and why modern human populations vary in certain physical features. Anthropologists are enthusiastic to understand how and why societies in the past and present differentiate in their customary ideas and practices. There is both theoretical and practical or applied aspect of anthropology. Theoretical anthropologists delineate conceptual model, theories and explain the rationale behind human acts. While applied anthropologists put anthropological methods, information an